Opportunities for membrane technology in controlled environment agriculture - Safari, Parisa; Rahnema, Hamed; Lipscomb, Glenn (Frontiers in Membrane Science and Technology, 2024)
Controlled environment agriculture has the potential to enhance agriculture sustainability, a United Nations sustainable development goal. Enclosed agricultural facilities can be used in locations that cannot support field agriculture while reducing water usage and increasing productivity relative to open field agriculture. The primary challenges with operation arise from energy consumption to maintain the proper growth conditions. Membrane processes can reduce energy consumption by controlling temperature, humidity, and carbon dioxide concentration. Membrane processes also can minimize water consumption by enabling the use of non-conventional water resources and reducing wastewater production. The literature describing these applications is reviewed and opportunities for future innovation are discussed.